Examining the impact of digital storytelling and video-assisted instruction on speaking performance across self-regulated learning levels in an ESP context - Dewi, Desi Surlitasari; Saptiany, Shella Gherina; Ria, Tiara Nove (Journal on English as a Foreign Language, 2025)
Recent advances in technology-enhanced language learning (TELL) emphasize innovative methods to improve speaking skills in English for specific purposes (ESP) classes, particularly for Law students. However, research comparing the effectiveness of digital storytelling (DST) and video-assisted instruction (VAI) in developing speaking performance remains limited, particularly in relation to students' self-regulated learning (SRL) levels. This study explores the impact of DST and VAI on speaking performance across SRL levels through a quasi-experimental research design. A total of 48 undergraduate ESP students majoring in Law at a private university in Indonesia were categorized into higher and lower self-regulation groups. The data were collected through an SRL questionnaire and speaking tests and analyzed using two-way ANOVA and independent samples t-tests. The results revealed that students in the DST group significantly outperformed those in the VAI group (Sig. = 0.009). However, no significant interaction effect was found between SRL, instructional approach, and speaking proficiency. The finding implies that DST enhances speaking proficiency by combining structured oral production with creative narrative development, requiring students to rehearse, refine, and integrate linguistic elements in an authentic context. EFL teachers should integrate DST in their classes to improve communication skills in professional and academic settings.